2022
DOI: 10.1186/s12887-022-03121-8
|View full text |Cite
|
Sign up to set email alerts
|

Presurgical time and associated factors as predictors of acute perforated appendicitis: a prospective cohort study in a teaching pediatric hospital in Colombia

Abstract: Background We aim to determine the association between out and in-hospital factors with time, from the beginning of the symptoms to the surgery, in patients with acute appendicitis treated at Fundación Hospital Pediatrico La Misericordia (HOMI) in Colombia. Methods Eleven month prospective cohort study of pediatric patients at HOMI with acute appendicitis diagnosis taken to surgery. Data from the out-of-hospital phase was collected by surveying par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…This estimate includes perforated appendicitis, as well as any 30-day revisits to give a more realistic cost comparison because patients present with perforated appendicitis for many reasons other than delayed diagnosis. 29 , 30 , 31 Appendicitis is diagnosed for 292 297 patients annually in the US. 32 A 2.7% rate of delayed diagnosis will impact 7892 patients annually and, given the mean marginal cost difference is $2712.45, this leads to $21 406 655 of preventable cost from poor diagnostic quality every single year.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…This estimate includes perforated appendicitis, as well as any 30-day revisits to give a more realistic cost comparison because patients present with perforated appendicitis for many reasons other than delayed diagnosis. 29 , 30 , 31 Appendicitis is diagnosed for 292 297 patients annually in the US. 32 A 2.7% rate of delayed diagnosis will impact 7892 patients annually and, given the mean marginal cost difference is $2712.45, this leads to $21 406 655 of preventable cost from poor diagnostic quality every single year.…”
Section: Discussionmentioning
confidence: 96%
“…This estimate includes perforated appendicitis, as well as any 30-day revisits to give a more realistic cost comparison because patients present with perforated appendicitis for many reasons other than delayed diagnosis. [29][30][31] Appendicitis is diagnosed for 292 297 patients annually in the US. 32…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are in line with the multivariate analysis of other studies where it has been established that this factor is one of the most frequently identified as a predictor of perforation. 21,22,24,[27][28][29] Concerning clinical variables, the only symptom associated with perforated appendicitis that remained significant in the multivariate analysis was the presence of emesis in the questioning on admission to the emergency department (OR=4.28, 95%CI: 1.63-11.21). Regarding clinical signs during physical examination, temperature >38.3ºC and tachycardia also had a positive association with perforation, which is partly in line with what has been reported in the literature, where fever has been associated with an increased risk of this outcome in the pediatric population, 4,24,27 but no association with tachycardia has been described.…”
Section: Discussionmentioning
confidence: 99%
“…Acute appendicitis (AA) is the most common abdominal surgical pathology in the pediatric population [1,2]. The clinical manifestations and imaging findings may vary according to age, sex, underlying pathological conditions, and the development of complications, including perforation [3][4][5][6]. It has been suggested that the appendix location may affect the disease's overall behavior, although no studies confirm this.…”
Section: Introductionmentioning
confidence: 99%